Longitudinal bidirectional association between youth electronic cigarette use and tobacco cigarette smoking initiation in Thailand - Patanavanich R. (2023)
Introduction: This study quantifies the longitudinal association between e-cigarette use and subsequent conventional cigarette initiation and vice versa among Thai youths. Methods: Data from a longitudinal survey of 6045 Thai seventh grade students with baseline in 2019 and the 12-month follow-up in 2020 were analysed using complex survey multivariate logistic regressions to assess whether e-cigarette use was associated with subsequent cigarette smoking (ever, current and dual product users at follow-up) among baseline never smokers. Results: Consistent with prior findings from other countries, among those who had never smoked cigarettes at baseline, ever e-cigarette users were more likely to try cigarette smoking (adjusted OR 4.44; 95% CI 2.23 to 8.86; p<0.001), or become dual users (adjusted OR 5.31; 95% CI 2.63 to 10.74; p<0.001) 1 year later. Baseline current e-cigarette users were more likely to become ever smokers (adjusted OR 5.37; 95% CI 1.82 to 15.90; p=0.005), current smokers (OR 3.92; 95% CI 1.69 to 9.14; p=0.003) and dual product users (adjusted OR 6.96; 95% CI 1.54 to 31.38; p=0.015) at the 12-month follow-up than non-e-cigarette users. Similarly, among never e-cigarette users at baseline, ever cigarette smoking were more likely to try e-cigarettes (adjusted OR 3.38; 95% CI 1.66 to 6.88; p=0.002), currently use e-cigarettes (adjusted OR 2.75; 95% CI 1.47 to 5.13; p=0.003) and currently use both e-cigarettes and cigarettes (adjusted OR 4.87; 95% CI 2.92 to 8.13; p<0.001) at the follow-up than never smokers. Among never e-cigarette users at baseline, current-cigarette smoking were more likely to try e-cigarettes (adjusted OR 6.21; 95% CI 2.58 to 14.95; p<0.001), currently use e-cigarettes (adjusted OR 2.80; 95% CI 1.27 to 6.14; p=0.014) and currently use both e-cigarettes and cigarettes (adjusted OR 7.70; 95% CI 3.45 to 17.19; p<0.001) at the follow-up than never smokers. Conclusions: This longitudinal study in Asian low-income and middle-income countries supports the prospective association of youth e-cigarette use with subsequent smoking initiation and youth cigarette use with subsequent e-cigarette initiation that is similar to that observed in high-income Western countries.